Supply Chain Information Model for Revenue Collection of the Excise Department in Thailand - Artaphon Chansamut (ExcelingTech, 2023)
The purpose of this research aim to develop supply chain information model for Revenue collection of the excise department in Thailand. Theresearch was conducted with research and development method using questionnaires, and the model was assessed by experts. The research found there were four type the supply chain information model for Revenue collection of the excise department in Thailand namely main elements , Supplier, the excise department, and Customers. The data analysed by using arithmetic mean and standard deviation . supply chain information model for Revenue collection of the excise department in Thailand using Back-Box technique. The results from experts have evaluated the model and commented that the model is high level and can be used to develop information system.